2016
DOI: 10.1016/j.cell.2016.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Expression of Specific tRNAs Drives Gene Expression and Cancer Progression

Abstract: SUMMARY Transfer RNAs (tRNAs) are primarily viewed as static contributors to gene expression. By developing a high-throughput tRNA profiling method, we find that specific tRNAs are upregulated in human breast cancer cells as they gain metastatic activity. Through loss-of-function, gain-of-function, and clinical-association studies, we implicate tRNAGluUUC and tRNAArgCCG as promoters of breast cancer metastasis. Upregulation of these tRNAs enhances stability and ribosome occupancy of transcripts enriched for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
345
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 393 publications
(408 citation statements)
references
References 37 publications
14
345
2
3
Order By: Relevance
“…2 Other research groups have also reported dramatic and significant effects of single tRNA transfection, 4 , 6 , 7 and we confirmed the same results in stable NIH3T3 MEF cells, where a single copy of tRNA Leu CAG was inserted in the genomic region (Fig. 6A-C and Fig.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…2 Other research groups have also reported dramatic and significant effects of single tRNA transfection, 4 , 6 , 7 and we confirmed the same results in stable NIH3T3 MEF cells, where a single copy of tRNA Leu CAG was inserted in the genomic region (Fig. 6A-C and Fig.…”
Section: Discussionsupporting
confidence: 89%
“…17 A recent study had revealed that breast cancer metastasis was promoted by tRNA Glu UUC and tRNA Arg CCG . 4 This study demonstrated that overexpression of specific tRNAs could modulate protein expression in a codon-dependent manner, resulting in metastatic behavior. It also shed light on the importance of quantitative changes in tRNAs.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations